MAIN TRENDS OF GENERAL LINGUISTIC EVOLUTION OF THE ENGLISH LITERARY LANGUAGE - Kurban B.Shadmanov (Scholar Express Journal, 2024)
The article deals with the main trends of general linguistic evolution of the English literary language (XYI-XYII cc.). The author discusses a more complicated way the Literary English undergone as to the formation of scientific and philosophical vocabulary in the XVI-XVII centuries in England, on the one hand, took place under the influence of the national specifics of socio-economic and cultural development, and on the other, it reflected the main trends of general linguistic evolution despite the presence of two contradictory and opposite directions - purism, on the one hand, and the widespread use of Latinisms to create missing terms, on the other. Both the first and second directions are indicated by the conscious nature of the struggle for a particular language policy.
Keywords: linguistic; evolution; trend; philosophy